Applying Clean and Healthy Behavior By Wudhu For Health Benefits - Andriyani Andriyani (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2021)
Wudu is a process of cleanliness performed by a person to wash body parts five times a day. Wudu itself contains two aspects of cleanliness; namely, physical cleanliness in the form of washing the human body parts, and the inner cleanliness caused by the influence of ablution to humans in the form of cleansing from mistakes and sins committed by the parts of the body. Islam teaches us to maintain health in any case, both physical and mental health, one example is by Wudu. Wudu is a very important Islamic teaching and is a legal requirement for praying. In addition, the harmonies and sunnahs of Wudu provide very important benefits for the health of human body. This study is a literature review by reviewing journals on Wudu, health, Clean and Healthy Behavior. This research is descriptive - analysis, which is a form of research by describing the data obtained from collected literature sources. Based on the results of the review, it was found that there are various kinds of benefits of Wudu in a good & correct way for the health of the body.